Simulakra Bahasa Agama Da’i Milenial di Media “TikTok” - Sa'ad, Mukhlisin; Baharun, Hasan; Istifa, Fera Ailinia (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2020)
The growing social media provides new communication patterns in current Islamic preaching (da’wah). This research focuses on religious language usage in the social media “Tiktok” by millennial da’i (Muslim proselytiser), in particular for da’wah purposes. This study has applied a qualitative descriptive and phenomenological approach. The results reveal that a simulation of religious languages used by da’i in Tiktok application has created multiple interpretations, wherein media users are invited to think critically in digesting chapter by chapter of the provided discussions, and some even lead to apostasy. Therefore, this article argues that religious language practiced in social media should meet the religious propagation ethics.